An explorative study on consequences of abuse on psychological wellbeing and cognitive outcomes in victims of gender-based violence - Lausi, Giulia; Cricenti, Clarissa; Mari, Emanuela; Burrai, Jessica; Quaglieri, Alessandro; Giannini, Anna Maria; Barchielli, Benedetta (Frontiers in Psychology, 2024)
Background The issue of gender-based violence has been a public health problem for years. Considering its systemic nature, the possible consequences at the individual level on the psychological and cognitive wellbeing of victims have been examined. The present research aims to explore the differences in the various types and forms of violence. Methods A non-probability and convenience sample was used; a total of 83 participants joined the research. Inclusion criteria were minimum age of 18 years, female gender, and knowledge of the Italian language. Two non-parametric One-Way ANOVAs (Kruskal-Wallis) were performed according to the type of violence experienced and the type of self-reported abuse (i.e., no victimization, single victimization, complex victimization). Results and discussion Results showed that victims of violence scored higher overall than non-victims on all subscales of the Depression, Anxiety, Stress Scale. Analyses among the three groups-no violence, single violence, and complex violence-showed no differences in any of the dimensions between those who experienced single and complex violence, while differences emerged between the “no victimization” group and the other groups. The results were discussed in relation to the existing literature on the topic, highlighting the limitations and future applications of the collected data.